Strategi Pengembangan Agribisnis Komoditas Cabai di Kota Makassar - Patima, Nur; Kamaruddin, Citra Ayni; Hastuti, Diah Retno Dwi; Rahim, Abd. (Universitas Galuh, 2024)
Urban farming is an attempt to utilise the limited space available in urban areas for ecological, aesthetic, financial purposes and to fulfil food needs in urban areas. Urban farming in Makassar City is developed by forming farmer women groups (KWT) in each alley by producing a variety of commercially useful crops, such as chillies. Chilli is an important commodity as it is a major contributor to inflation. To increase the availability, quantity and quality of chillies, urban agriculture has the potential to become a platform for agribusiness development. This research aims to identify internal and external environmental conditions, formulate and determine priority strategies in the development of urban farming-based agribusiness of chilli commodities in Makassar City. This research was approached with SWOT analysis and Analytic Hierarchy Process (AHP). The results showed that the agribusiness development strategy is in quadrant I (Growth oriented strategy) with alternative priorities namely improving the quantity and quality of chilli production through the use of assistance and technology, increasing the motivation of KWT members, maximising the use of technology by utilising cultivation and processing technology and collaborating with other KWT.